DEVELOPMENT OF MODERN MECHANISM OF FORMATION OF GOVERNMENT PROCUREMENT FOR THE BENEFIT OF DEVELOPMENT OF EKOORIENTED PROCESSES - A. Gukasova; S. Kiseleva (Вестник университета)
Procurement is a necessary component of the activities of each organization. Procurement should be holistic, reflect a systematic process, the purpose of which is with minimal effort and money in a timely manner to get all the goods, works and services, which are necessary for the organization. The article reveals the relevance and importance of the environmental component of tenders, analyzes the methods of procurement, provides recommendations in terms of non-price evaluation criteria, and offers options for the implementation of the environmental concept in Russia.